Formative and professional narratives of a transsexual teacher - Dias, Alfrancio Ferreira (Educar em Revista, 2018)
In this text, we reflect on the formative process and the professional performance of a transsexual teacher, based on the policies of bodily subjectivity and gender inscribed in the field of education. As for methodology, a qualitative post-critical approach was used, through the accomplishment of narrative interview. The narratives contribute to the beginning and/or development of the deconstruction of educational practices marked by the principle of normative regulation, stating that education can also be a field of (dis)learning of gender regulations, through the insertion, permanence and destabilization that transsexuals, as people, perform.